Legal arbitration in business cases, an impetus for development (Research, Society and Development, 2021)
The successive increase in commercial relations leads to an increase in litigation and conflicts related to signed contracts. Thus, it is natural that the solution to these problems requires the presence of neutral third parties, so that greater legal certainty is guaranteed. Usually in Brazil, state jurisdiction is used as a neutral third party, in the form of the Judiciary. It happens that, for some time, it has been worn and lethargic, causing damage to the parts involved. In addition to this factor, arbitration is a tool capable of bringing together the laws of different countries in a friendly way, a fact of extreme importance in the context of the growing international relations in which Brazil finds itself. Legal arbitration as an alternative form of conflict resolution finds space to effectively resolve such conflicts. Progressively, with technological advances, arbitration also operates online. This paper seeks to analyse legal arbitration as a means of conflict resolution in the current scenario, as well as to seek to understand how technological innovation brings new guidelines for this alternative means of conflict resolution.